Travellers’ perception on airline alliances perceived value / Nor Hisyam Seliman, Norzuwana Sumarjan and Salleh Mohd Radzi - Seliman, Nor Hisyam; Sumarjan, Norzuwana; Mohd Radzi, Salleh (Faculty of Hotel & Tourism Management, Universiti Teknologi MARA, 2023)
Air transportation significantly contributes to the movement of people between regions, covering vast distances and connecting service providers. Nevertheless, one airline cannot cater all the destinations that a traveller requires. Therefore, airline alliances have been formed to enlarge market and better fulfil travellers’ requirements and demands. To ensure competitiveness, most of the alliances had enhance their strategy to enhance the value of their alliances. There are various dimensions of perceive value, however, which are the most agreeable dimension that can help to improve customer satisfaction and loyalty. This study voids the gap by examining the dimensions that could help the alliance airlines to better retain in the market. Self-administered questionnaires had been distributed using convenience sampling travellers above 20 years old with travel experience boarding at least one airline under the three airline alliances. Two hundred and sixty-two questionnaires were collected and analysed using descriptive analysis. Six dimensions of airline alliances perceived value has been tested, which include i) network extension, ii) frequent flyer program, iii) price competitiveness, iv) psychosocio benefits, and v) general attitude towards alliances, and vi) safety and security. This study found that perceived network extension dimensions was the mostly agreed dimension followed by perceived safety and security and general attitude dimensions. It is hoped that this study could assist the airline alliance operators to investigate and better strategize their resources in satisfying their customer and widening their market share.